Orientation for New Faculty About Tenure and Promotion: Standards and the Review Process. Issue 4 (1st October 2016) - Belliston, C. Jeffrey
Column Editor's Notes: This feature column, written by C. Jeffrey Belliston from Brigham Young University (BYU) in the United States of America (USA) takes up the challenge issued in the inaugural Library Workforce column. The article discusses the collegial process for tenure and/or promotion and highlights a critical process in the life cycle of the academic librarian. Using the lens of the BYU experiences, Belliston overviews and discusses tenure and promotion processes, which can be for the academic librarian with faculty status, both a familiar process and at the same time, an equally mysterious and stressful process. Beyond the library at the institutional level, the tenure and/or promotion process recognizes and establishes the academic librarian as part of The Academy. Imbedded in the process is shared responsibilities for the academic librarian, the library and the institution to work together to ensure career progression and success. For example, the University of Saskatchewan in Canada recognizes the status and importance of both processes in university-level standards, prefaced with following acknowledgement and commitment:The award of tenure represents a long-term commitment of the university to a faculty member. It is a status granted as a result of judgement, by one's peers, on both the performance of academic duties and the expectation of future accomplishments. Promotion of colleagues involves an assessment of their success in performing their academic duties and an evaluation of the likelihood of future accomplishments (University of Saskatchewan Standards for Promotion and Tenure, accessed at: http://library.usask.ca/info/libstandards2015.pdf). I invite further contributions on this or related lifecycle topics. Please submit articles for this column to the editor at vicki.williamson@usask.ca ABSTRACT: In her inaugural column, "The Library Workforce" editor Vicki Williamson wrote of various frameworks through which we can consider library workforce issues. One of these is the lifecycle framework. In academic institutions where professional librarians have faculty status with the possibility of tenure and promotion, the process of being granted tenure and being promoted to a higher rank is a significant, and often stressful, part of the librarian lifecycle. This column describes university and library efforts made to help newly hired faculty in the Harold B. Lee Library at Brigham Young University be successful in achieving tenure and being promoted.